Hydrogen Barriers Based on Chemical Trapping Using Chemically Modulated Al2O3Grown by Atomic Layer Deposition for InGaZnO Thin-Film Transistors - Lee, Yujin; Nam, Taewook; Seo, Seunggi; Yoon, Hwi; Oh, Il Kwon; Lee, Chong Hwon; Yoo, Hyukjoon; Kim, Hyun Jae; Choi, Wonjun; Im, Seongil; Yang, Joon Young; Choi, Dong Wook; et al. (ACS Applied Materials and Interfaces, 2021)
In this study, the excellent hydrogen barrier properties of the atomic-layer-deposition-grown Al2O3 (ALD Al2O3) are first reported for improving the stability of amorphous indium gallium zinc oxide (a-IGZO) thin-film transistors (TFTs). Chemical species in Al2O3 were artificially modulated during the ALD process using different oxidants, such as H2O and O3 (H2O-Al2O3 and O3-Al2O3, respectively). When hydrogen was incorporated into the H2O-Al2O3-passivated TFT, a large negative shift in Vth (ca. -12 V) was observed. In contrast, when hydrogen was incorporated into the O3-Al2O3-passivated TFT, there was a negligible shift in Vth (ca. -0.66 V), which indicates that the O3-Al2O3 has a remarkable hydrogen barrier property. We presented a mechanism for trapping hydrogen in a O3-Al2O3 via various chemical and electrical analyses and revealed that hydrogen molecules were trapped by C-O bonds in the O3-Al2O3, preventing the inflow of hydrogen to the a-IGZO. Additionally, to minimize the deterioration of the pristine device that occurs after a barrier deposition, a bi-layered hydrogen barrier by stacking H2O- and O3-Al2O3 is adopted. Such a barrier can provide ultrastable performance without degradation. Therefore, we envisioned that the excellent hydrogen barrier suggested in this paper can provide the possibility of improving the stability of devices in various fields by effectively blocking hydrogen inflows.
Keywords: Amorphous indiumgallium-zinc oxide (a-IGZO) thin-film transistor (TFTs); Barrier deposition; Chemical species; Chemical trapping; Electrical analysis; Hydrogen barriers; Hydrogen molecule; Negative shift; A-IGZO; Al2O3; atomic layer deposition; hydrogen barrier; stability